Development of Learning Media Based on Google Web Sites on Animal Reproductive Topic to Increase Higher Order Thinking Skills - rozani azhar; arif sholahuddin; mella mutika sari (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2023)
This study aims to analyze the validity kamislot, practicality and effectiveness of web-based learning media google sites on reproductive material in animals to improve Higher Order Thinking Skills (HOTS). The method used in this research is Research and Development with a 4D development model. Data collection techniques are using validation sheets of media experts and material experts; student response questionnaire; and test instruments for reproductive knowledge in animals. The research subjects were six students in class IX C in the small group trial and 24 students in class IX D in the large group trial held at MTs Ibtidaussalam, Barito Kuala Regency. The results showed that the learning media developed in category (1) was very valid based on the assessment of media and material experts with an average validity score of 0.88 (2) very practical based on the assessment after testing to students with a practicality score of 90.89% and (3) effective based on learning outcomes of learning outcomes of reproductive material in animals by students with an N-gain score of 0.76. Based on the results of these studies, it can be concluded that the web-based learning media google sites material reproduction in animals is very suitable for students to use to increase HOTS.